(untitled) (Research, Society and Development, 2021)
The ora-pro-nobis is part of a group of unconventional vegetables that are not usually found on menus due to the population’s lack of knowledge about its nutritional benefits. However, unconventional food plants stand out as functional foods due to vitamins, antioxidants, fibers, protein and minerals found in plants, as is the case of ora-pro-nobis. The present work had the main intention to elaborate an extruded corn snack with addition of ora-pro-nobis leaf meal (OPN) of the species Peréskia grandifolia Haw (PG), aiming to increase the nutritional value of this product and evaluate its sensorial acceptance to untrained evaluators. Harvesting, cleaning and dehydration were carried out to obtain the leaf flour. Subsequently, this flour was subjected to routine bromatological analyzes such as moisture, proteins, lipids, ash, iron and fibers, with results close to those found in the literature. With the leaf flour, two formulations were developed with the addition of 10 and 20% leaf flour respectively, together with a composition standard of 100% corn grits. The finished products were subjected to the same bromatological analyzes previously mentioned, in addition to a sensory analysis of acceptance by Hedonic scale with untrained tasters. The supplement developed from ora-pro-nobis leaves showed high biological value in fiber proteins in addition to good acceptance, proving viable its use.